REMOTE VISION EXPERIMENTS: A PHOTO ROMAN. Issue 1 (2nd January 2019) - Unknown
Abstract: This work considers the ways in which, throughout human history, maps have defined our limits as much as charted our exploration. These images act as a kind of ghost vision – a spectral overlay of the world created and accessed as data sets, satellite imagery, and geopolitical mapping, merged in an algorithmically generated 3D mesh. This brings with it a view of the world in which complementary and competing navigational vectors collage and collide. Yet, for all its apparent hyper-modern otherness, its novelty and dexterity is still oriented around and contingent upon the temporal and electromagnetic limits of our biological inheritance.